Vegetable farmers and Malaysian certification scheme of good agricultural practices (MyGAP): opinions and barriers - Gom, Elina W.; Rezai, Golnaz; Mohamed, Zainal Abidin; Sharifuddin, Juwaidah (INSInet Publications, 2015)
The demand for quality, safety and environmental-friendly fresh produce, especially vegetables, is growing among Malaysian consumers. In response to this, the government has introduced Malaysian certification scheme for Good Agricultural Practices (MyGAP) to farmers in the perks of encouraging them to practice good agricultural practices in their farms. Although the government has provided a lot of extensions, training and complimentary process for MyGAP application, the uptake among Malaysian vegetable farmers is still low and slow. Objective: This study is therefore conducted to explore the latent factors that influence the vegetable farmers’ failure to apply MyGAP. This group of farmers play an essential role in shaping the rising trend in producing high quality vegetables in Malaysia. Results: Descriptive analysis and factor analysis were used in this study and the factors that were extracted from the factor solution were barriers, underlying values, personal norms, knowledge and affirming attitude. Conclusion: These latent factors mentioned play a relatively high importance in determining the vegetable farmer’s opinion and barriers in endorsing MyGAP.